Adoption of Dairy Farming Technologies by the Farmers of Nagaur District of Rajasthan - Kumawat, S. R. and Verma, M. P., (Indian Journal of Extension Education, 2016)
The present study was conducted in Nagaur district of Rajasthan to know the adoption level of farmers regarding dairyfarming technologies. In all 180 farmers were selected randomly from three block of the Nagaur district. The result of thestudy indicated that adoption level of farmers regarding improved breed of buffalo (45 %), Dry fodder (86 %) feeding ofconcentrate during lactation (45%) chaffing of fodder (58 %) colostrums feeding to newly born calves (47 %), anddrinking water (72%) were quite high. The adoption of dairy farming technologies was positively and significantly relatedwith thirteen independent variables viz. Age, Education, Family size, dairy experience, organization participation, landholding, livestock possession, annual income, economic motivation, market orientation, scientific orientation andknowledge of improved dairy management practices at 0.01 level probability